Clinical Relevance of Body Fluid Volume Status in Diabetic Patients With Macular Edema - Yao, Jie; Peng, Qingsheng; Li, Yuanhong; Liang, Anyi; Xie, Jianteng; Zhuang, Xuenan; Chen, Ruoyu; Chen, Yesheng; Wang, Zicheng; Zhang, Liang; Cao, Dan (Frontiers in Medicine, 2022)
Objective: To investigate body fluid status in diabetic macular edema (DME) patients and the extent to which it is affected by renal function. Methods: One hundred and thirty-two eyes from 132 patients with diabetes mellitus (DM) were prospectively collected in this cross-sectional, observational study. Thirty-five were DM patients without diabetic retinopathy (DR), 31 were DR patients without DME, and 66 were DME patients. The fluid status of each participant was quantified with extracellular water-to-total body water ratio (ECW/TBW) using a body composition monitor. Central subfield thickness (CST) and macular volume (MV) were obtained using optical coherence tomography (OCT). Urine albumin-to-creatinine ratio (UACR), estimated glomerular filtration rate (eGFR), and albumin was obtained using serum and urine laboratory data. Results: ECW/TBW was significantly increased in DME patients (39.2±0.9, %) compared to DM (38.1±0.7, %, P=0.003) and DR patients without DME (38.7±0.9, %, P<0.001). In multilinear regression, fluid overload was positively related to DME and UACR (DME vs. DM: β=2.418, P<0.001; DME vs. DR: β=1.641, P=0.001; UACR, per 10^2, β=1.017, P=0.01). In the binary logistic regression for DME risk, the area under the receiver operating characteristic curve (AUROC) increased significantly by adding ECW/TBW along with UACR and age (AUC: 0.826 vs. 0.768). Conclusions: DME patients had elevated body fluid volume independent of kidney functions. The assessment of extracellular fluid status may help in the management of DME.